Effectiveness of Online Mathematics Learning during Covid-19: Empirical Evidence from a Tertiary Institution in Ghana - Loretta Arhin-Larbi; Christopher Owu-Annan (CV FOUNDAE, 2023)
The Covid-19 pandemic prompted a global shift to online education, posing unique challenges for mathematics instruction. This study investigates undergraduate mathematics students' perceptions of the effectiveness of online teaching strategies and the challenges they faced during the Covid-19 era. Using a pragmatic paradigm and sequential explanatory design, data were collected through questionnaires and interviews. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed through content analysis. A simple random sampling technique was used to select 379 third-year mathematics students from Ghana's central region. The findings reveal that the combination of video, audio, and text-based materials was perceived as the most effective instructional strategy, while limited interaction between lecturers and students was the least effective. The primary challenge identified was limited internet access, which significantly hindered online learning experiences. The study highlights the importance of understanding students' perceptions to enhance online mathematics learning. It concludes that effective online instructional strategies are crucial for successful mathematics education. The study recommends continuous training for mathematics lecturers on effective online teaching methods, improved network connectivity from the telecommunication sector, and universities providing data-free access to online platforms to address internet challenges.